The The Role Of Von Willenbrand Factors As The Early Detection Of Endotel Cell Damage In Youth Ages With Obesity In The USU Medan Campus Environment - Syahputra, Muhammad; Suryani, Sry; Rusdiana (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2021)
Preliminary : Endothelial cells are a single layer that lines the entire vascular system. Endothelial dysfunction can be triggered by several main things, namely physical stress, oxidative stress and irritant substances. Obesity triggers an inflammatory process and metabolic disorders that will lead to increased oxidative stress. Long-term oxidative stress will cause damage to cells and tissues and trigger degenerative diseases. Damage to endothelial cells is expected to be detected by examining Von Willenbrand levels so that it can prevent complications of vascular disorders early. Method: This research is descriptive with cross sectional design. Carried out from March to October 2018 on the USU Campus. The first examination was done to measure body weight and height to determine body mass index, then performed lipid profile and blood sugar levels (KGD) in the sample, then examined von Willenbrand factor levels carried out in the integrated laboratory of USU FK using the method ELISA in both the sample group and the control group. The research subjects were adolescents aged 17-25 years with BMI> 25 kg / m2Data analysis was carried out using the T-Test statistical program, comparing two groups. Result: Of the 40 obese subjects found Von Wilenbrand level values ​​The lowest factor was 1.78 IU / ml and the highest was 35.60 IU / ml. Whereas in 40 non-obese subjects Von Wilenbrand grade values ​​were the lowest factor of 2.01 IU / ml and the highest was 45.10 IU / ml. This difference was not statistically significant (p = 0.661).Conclusion: There was no significant difference between the levels of Von Wilenbrand Factors in obese subjects with non-obese subjectsKey Words: Obesity, endothelial cells, Von Wilenbrand Factors